Hierarchically Nanostructured Hybrid Platform for Tumor Delineation and Image‐Guided Surgery via NIR‐II Fluorescence and PET Bimodal Imaging. Issue 45 (24th September 2019) - Zhang, Qing; Zhou, Huijun; Chen, Hao; Zhang, Xiao; He, Shuqing; Ma, Lina; Qu, Chunrong; Fang, Wei; Han, Yanjiang; Wang, Da; Huang, Yuanjian; Sun, Yueming; et al.
Abstract: Bimodal imaging with fluorescence in the second near infrared window (NIR‐II) and positron emission tomography (PET) has important significance for tumor diagnosis and management because of complementary advantages. It remains challenging to develop NIR‐II/PET bimodal probes with high fluorescent brightness. Herein, bioinspired nanomaterials (melanin dot, mesoporous silica nanoparticle, and supported lipid bilayer), NIR‐II dye CH‐4T, and PET radionuclide 64 Cu are integrated into a hybrid NIR‐II/PET bimodal nanoprobe. The resultant nanoprobe exhibits attractive properties such as highly uniform tunable size, effective payload encapsulation, high stability, dispersibility, and biocompatibility. Interestingly, the incorporation of CH‐4T into the nanoparticle leads to 4.27‐fold fluorescence enhancement, resulting in brighter NIR‐II imaging for phantoms in vitro and in situ. Benefiting from the fluorescence enhancement, NIR‐II imaging with the nanoprobe is carried out to precisely delineate and resect tumors. Additionally, the nanoprobe is successfully applied in tumor PET imaging, showing the accumulation of the nanoprobe in a tumor with a clear contrast from 2 to 24 h postinjection. Overall, this hierarchically nanostructured platform is able to dramatically enhance fluorescent brightness of NIR‐II dye, detect tumors with NIR‐II/PET imaging, and guide intraoperative resection. The NIR‐II/PET bimodal nanoprobe has high potential for sensitive preoperative tumor diagnosis and precise intraoperative image‐guided surgery. Abstract : To achieve sensitive diagnosis and precise resection of tumors, bimodal probes for the second near infrared window (NIR‐II) and positron emission tomography (PET) imaging are highly desired. Here, a nanoplatform (made from melanin, mesoporous silica nanoparticles, and supported lipid bilayer) is reported to construct enhanced NIR‐II and PET bimodal probes for tumor imaging and image‐guided resection in mice.